2019
DOI: 10.1016/j.heliyon.2019.e01761
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant capacity and hepatoprotective activity of myristic acid acylated derivative of phloridzin

Abstract: The antioxidant activities in vitro and hepatoprotective effects against carbon tetrachloride (CCl 4 ) induced acute liver injury in vivo of myristic acid acylated derivative of phloridzin (PZM) were investigated. The PZM was obtained by enzymatic acylation of myristic acid and phloridzin (PZ). The antioxidant capability of PZM in vitro was evaluated by the ferric reducing antioxidant power assay (FRAP), 2,2′-Azinobis- 3-ethylbenzthiazoline-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Phloridzin is a natural dihydrochalcone with various pharmacological effects, such as antioxidant, anti-inflammatory, anti-viral, antihypertensive, antihyperglycemic and anti-tumor activities. [1][2][3] The compound is found in many plants, particularly Malus species, being an active ingredient in herbal medicines. 4,5 However, its low aqueous solubility and poor enzyme inhibitory capacity have limited its application in functional foods and medicines.…”
Section: Introductionmentioning
confidence: 99%
“…Phloridzin is a natural dihydrochalcone with various pharmacological effects, such as antioxidant, anti-inflammatory, anti-viral, antihypertensive, antihyperglycemic and anti-tumor activities. [1][2][3] The compound is found in many plants, particularly Malus species, being an active ingredient in herbal medicines. 4,5 However, its low aqueous solubility and poor enzyme inhibitory capacity have limited its application in functional foods and medicines.…”
Section: Introductionmentioning
confidence: 99%
“…66 Rosmarinic acid, alpha-eleostearic acid, p-coumaric acid, myristic acid, diosmetin, and azelaic acid have also shown antioxidant activity based on several previous studies. [67][68][69][70][71][72] This study is the first to successfully profile metabolites and perform molecular docking, and the results are promising for anti-obesity and antioxidant functional foods based on in vitro validation and molecular docking results. However, this still needs further research i.e., isolation and purification of each observed compound and continuing in vivo trials in animal models prior to human clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…42) Moreover, myristic acid acylated derivative of phloridzin, which mainly occurred on the 6′-OH of phloridzin glycoside, was also demonstrated to have significantly higher total antioxidant activity than the parent phloridzin both in vitro and in vivo. 43) Thus it is speculated that the chlorogenic acid, procyanidin, epicatechin and phloridzin in AP all contributed to its strong antioxidant activities. In our study, it could be found that adding different concentrations of AP 24 h before H 2 O 2 treatment could effectively improve the activity of Caco-2 cells, maintain the cell morphology and significantly increase the number of viable cells (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%